Integrating Ketone and Glucose Monitoring for Optimized Diabetes Management: Key Ketone Monitoring Updates and Highlights from the ADA 2025 Conference [Podcast] - Kerr D (Diabetes, Metabolic Syndrome and Obesity, 2025)
David Kerr Center for Health Systems Research, Sutter Health, Santa Barbara, CA, USACorrespondence: David Kerr, Diabetes Research and Digital Health Equity, Sutter Center for Health Systems Research, 2121 N. California Ave, Suite 309, Walnut Creek, CA, 94596, USA, Email david.kerr@sutterhealth.orgAbstract: This article discusses innovations and advancements in diabetic ketoacidosis (DKA) and ketone monitoring technology from the 2025 American Diabetes Association (ADA) conference held from June 20– 23, 2025, in Chicago, Illinois. The session, “Continuous Ketone Monitoring—Innovations and Clinical Applications” featured four expert presentations from Drs. Ketan Dhatariya, Lori Lafell, Jennifer Sherr, and Richard Bergenstal, each addressing the clinical implications of physiology and the impact of ketosis and DKA on people with diabetes; methods to detect ketones and current approaches to prevent DKA; ketone sensor performance criteria and current study data; and the potential clinical impact of continuous ketone monitoring. The discussion concludes by discussing a poster presented at the ADA which discussed ketone profiles in free-living people with type 1 diabetes using continuous ketone monitoring. The article closes by underscoring the desire by both clinicians and patients for continuous ketone monitoring to become mainstream sooner rather than later.Keywords: American Diabetes Association, diabetic ketoacidosis, diabetes management, ketone monitoring, continuous ketone monitoring, type 1 diabetes, type 2 diabetes, beta-hydroxybutyrate